Surface microtopography modulates sealing zone development in osteoclasts cultured on bone. Issue 127 (28th February 2017) - Shemesh, Michal; Addadi, Lia; Geiger, Benjamin
Abstract : Bone homeostasis is continuously regulated by the coordinated action of bone-resorbing osteoclasts and bone-forming osteoblasts. Imbalance between these two cell populations leads to pathological bone diseases such as osteoporosis and osteopetrosis. Osteoclast functionality relies on the formation of sealing zone (SZ) rings that define the resorption lacuna. It is commonly assumed that the structure and dynamic properties of the SZ depend on the physical and chemical properties of the substrate. Considering the unique complex structure of native bone, elucidation of the relevant parameters affecting SZ formation and stability is challenging. In this study, we examined in detail the dynamic response of the SZ to the microtopography of devitalized bone surfaces, taken from the same area in cattle femur. We show that there is a significant enrichment in large and stable SZs (diameter larger than 14 µm; lifespan of hours) in cells cultured on rough bone surfaces, compared with small and fast turning over SZ rings (diameter below 7 µm; lifespan approx. 7 min) formed on smooth bone surfaces. Based on these results, we propose that the surface roughness of the physiologically relevant substrate of osteoclasts, namely bone, affects primarily the local stability of growing SZs.